Monte Carlo study of coherent scattering effects of low-energy charged particle transport in Percus-Yevick liquids - Tattersall, Wade J.; Cocks, Daniel G.; Boyle, Gregory J.; Buckman, Stephen J.; White, R.D. (American Physical Society, 2015)
We generalize a simple Monte Carlo (MC) model for dilute gases to consider the transport behavior of positrons and electrons in Percus-Yevick model liquids under highly nonequilibrium conditions, accounting rigorously for coherent scattering processes. The procedure extends an existing technique [Wojcik and Tachiya, Chem. Phys. Lett. 363, 381 (2002)CHPLBC0009-261410.1016/S0009-2614(02)01177-6], using the static structure factor to account for the altered anisotropy of coherent scattering in structured material. We identify the effects of the approximation used in the original method, and we develop a modified method that does not require that approximation. We also present an enhanced MC technique that has been designed to improve the accuracy and flexibility of simulations in spatially varying electric fields. All of the results are found to be in excellent agreement with an independent multiterm Boltzmann equation solution, providing benchmarks for future transport models in liquids and structured systems.